2017
DOI: 10.1016/j.micromeso.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures and gas adsorption behavior of new lanthanide-benzene-1,4-dicarboxylate frameworks

Abstract: Six new lanthanide metal organic complexes, i.e. [La2(NO2-BDC)3(H2O)4] (1)[Ln(L)0.5(NO2-BDC)(H2O)] • 3H2O (Ln = Eu (2), Tb (3), Dy (4) and Ho (5); L = BDC 2or BDC 2-/NO2-BDC 2-) and [Tm(NO2-BDC)1.5(H2O)]•H2O (6), have been synthesized using mixed ligands of benzene-1,4-dicarboxylic acid (H2BDC) and the in situ generated 2-nitrobenzene-1,4-dicarboxylic acid (NO2-BDC 2-). Single crystal structures and topologies of the complexes are presented based on the single crystal X-ray diffraction and spectroscopic data.W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Owing to the substitutional disorder, atoms O8, O9, O13, and O19 were attributed to both The in situ generation of nitrite from nitrate can be assumed under the highly acidic solvo-/hydrothermal conditions (Figure S5). 27,44 The other partially occupied di-nitro-BPDC 2− exhibits similar substitutional disorder but with water molecules, leading to the possibility for atoms O10, O25, O28, and O34 to be from both carboxyl groups, i.e. O25−C28−O28 and O10−C41−O34, and four independent water molecules.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Owing to the substitutional disorder, atoms O8, O9, O13, and O19 were attributed to both The in situ generation of nitrite from nitrate can be assumed under the highly acidic solvo-/hydrothermal conditions (Figure S5). 27,44 The other partially occupied di-nitro-BPDC 2− exhibits similar substitutional disorder but with water molecules, leading to the possibility for atoms O10, O25, O28, and O34 to be from both carboxyl groups, i.e. O25−C28−O28 and O10−C41−O34, and four independent water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the nitro group should also be considered for the benefit of CO 2 adsorption. 27 On the basis of a literature survey, 29−32 few nanoporous frameworks of lanthanides can be afforded by using H 2 BPDC and its derivatives, although the successful synthesis depends critically on the synthesis conditions. Apparently, H 2 BPDC and its derivatives such as 2,6,2′,6′-tetranitrobiphenyl-4,4′-dicarboxylic acid can also provide flexible frameworks with substantial stability upon a change in guest molecules.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…123 Also, in IRMOF series and in MTV-MOF-5-EHI, the incorporation of NO 2 groups was a common technique for best-performing CO 2 adsorption. 124,125 The insertion of different functional groups in UiO-66(Zr)-X (X = -Br, -NH 2 , -NO 2 , -(CF 3 ) 2 , -(OH) 2 , -SO 3 H, and -CO 2 H) suggested that, in accordance with the polarity trend of the functional group, SO 3 H and CO 2 H groups possess the highest CO 2 selectivity, good working capacities, and medium-ranged CO 2 adsorption enthalpy. Additionally, the geometry of the UiO-66(Zr)-SO 3 H and UiO-66(Zr)-CO 2 H allows direct interaction between the inserted groups and CO 2 .…”
Section: Othersmentioning
confidence: 99%